HUBUNGAN SIKAP REMAJA DAN TINGKAT PENGETAHUAN TENTANG KESEHATAN REPRODUKSI TERHADAP KEJADIAN SEKS BEBAS PADA REMAJA DI SEKOLAH MENENGAH ATAS NEGERI 2 SUNGAI PENUH - Ulia, Azma (Menara Ilmu, 2019)
The young generation is the backbone of the nation, which is expected in the future to continue the nation's leadership baton for better. Knowledge of sexual and reproduction health really influence teen sex behavior. Because of lack of knowledge about sex can make teens become more curious and even tend to try themselves. This study aims to determine the relationship of attitudes and level of knowledge about reproductive health with the incidence of free sex in adolescents in Senior High School 2 Sungai Penuh in 2017. Descriptive analytical research design with cross sectional approach. Large sample 116 people with RandomSampling technique. The result of this research shows that there is a relationship of attitude with the occurrence of free sex with p-value = 0,043 (p <0,05) and the relation of knowledge level about reproductive health with free sex occurrence in adolescent in Senior High School 2 with p-value = 0.032 (p <0.05). Keywords: Attitude, Knowledge, Free Sex Event References: 20 (2002 - 2017)